1987
DOI: 10.1161/01.str.18.6.1087
|View full text |Cite
|
Sign up to set email alerts
|

Expanding cerebellar lacunes due to dilatation of the perivascular space associated with Binswanger's subcortical arteriosclerotic encephalopathy.

Abstract: An 80-year-old hypertensive woman developed right hemiplegia and died 24 hours after admission. Neuropathologic examination revealed multiple cerebral infarcts of various ages and diffuse subcortical arteriosclerotic encephalopathy. Clusters of asymptomatic "expanding" lacunes, due to dilatation of the perivascular spaces, were found in both dentate nuclei. These cavities, which presented as space-occupying lesions, were surrounded by a single layer of flattened cells and contained 1 or more sections of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 9 publications
2
26
0
1
Order By: Relevance
“…For example, the presence or absence of a hyperintense rim around CSFlike lesions on fluid-attenuated inversion recovery images 41 is not always helpful to discriminate small infarcts from dVRS, because astrocytic gliosis have been observed postmortem around large dVRS. 35,42 The use of proton density sequences for separating infarcts from dVRS based on the CSF signal 3 could also be inefficient because both cavitated infarcts and dVRS are filled with fluid. 39,43,44 The imaging analysis of the shape of cavities was recently shown to be crucial in the discrimination of dVRS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the presence or absence of a hyperintense rim around CSFlike lesions on fluid-attenuated inversion recovery images 41 is not always helpful to discriminate small infarcts from dVRS, because astrocytic gliosis have been observed postmortem around large dVRS. 35,42 The use of proton density sequences for separating infarcts from dVRS based on the CSF signal 3 could also be inefficient because both cavitated infarcts and dVRS are filled with fluid. 39,43,44 The imaging analysis of the shape of cavities was recently shown to be crucial in the discrimination of dVRS.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of contrast enhancement of the lesions and nearby parenchyma on MR imaging in our cases and in the case reported by Homeyer, et al, [10] however, is at variance with this hypothesis. Moreover, vasculitis was not present in the two other cases of expanding lacunae that have been verified by pathological investigation, [4,7] in which multiple cerebral infarctions and sclerohyalinotic vascular changes secondary to long-standing arterial hypertension were documented. In the case reported by Homeyer, et al, [10] and in our cases, no brain vascular lesion, vascular risk factor, or evidence of systemic vasculitis was present.…”
Section: Discussionmentioning
confidence: 76%
“…A review of the literature yielded only two other cases of expanding lacunae confirmed by pathological examination, [4,7] in which no clinical correlates of the lesions, located near the caudate and dentate nuclei, respectively, can be found in the brief case history provided. As well, no clinical correlate was found by Ogawa, et al, [17] in two cases of dilated perivascular spaces demonstrated by MR imaging in cerebral hemispheric white matter, although the results of a biopsy sample confirmed one of these cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However these symptoms do not relate to the locations of PVS, and do not follow the development of clinical symptom of patients [9,[25][26][27] .…”
Section: Clinical Symptoms Patients With Pvs In Above II Classmentioning
confidence: 99%